ON A POSSIBLE INFLATIONARY MODEL OF THE EARLY UNIVERSE - Avagyan, R.M.; Harutyunyan, G.H.; Sushkov, S.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2016)
We consider the inflationary regime of the expansion of the Universe within the framework of the modified Jordan theory. In this model, a specific cosmological scalar is an analog of the Einstein cosmological constant L, which is connected with the Hubble parameter by the power-law $φ(Φ) = α H^4$. As a result, a stage of hybrid inflation is obtained, at the end of which the acceleration parameter becomes zero.
Keywords: inflation, scalar-tensor theory of gravitation